Real-Time Wi-Fi Signal Monitoring from a User Perspective in a Wireless Environment Using the Internet of Things - Ibrahim, Mohd Zaki; Megat Muhammad Ridzuan; Inn, Arbaiah; Hassan, Rosilah (Universitas Islam Indonesia, 2023)
Mobility issues, such as handover, should be considered in a wireless environment. Real-time Wi-Fi monitoring from a user perspective is important because it is used to keep track of the Wi-Fi performance and status. Thus, improving network efficiency allows users to work more efficiently. The monitoring currently being held on the Wi-Fi is not in a real-time perspective. The monitoring is only focused on the connection between the controller and the Access Point (AP) and the AP to the user devices. We proposed a way to monitor the Wi-Fi from a real-time user perspective in a wireless environment. This project will use the Raspberry Pi as a device (RP). This is because RP has an operating system that can replace personal computers in terms of monitoring the access point from the user’s point of view. This device will make monitoring tasks more efficient and faster for the user to identify the problems occurring at the Wi-Fi network. This research will also enable the usage of the existing Internet of Things (IoT) to develop new things. To conclude, monitoring using an IoT device can project the view of the Wi-Fi performance from a user perspective.